Effects of Melia azedarach extract on Cotesia ayerza, parasitoid of the alfalfa defoliator Colias lesbia - Valladares, Graciela Rosa (2011)
Extracts from the fruit of Melia azedarach L. (Meliaceae) have shown antifeedant and toxic effects on several insect species, including various pests, but the action of these compounds on natural enemies such as predators and parasitoids is less understood. The purpose of this work was to assess extract effects on Cotesia ayerza (Brèthes) (Hymenoptera: Braconidae), a parasitoid of the alfalfa defoliator Colias lesbia Fab. (Lepidoptera: Pieridae). The extract was first tested on butterfly larvae, in order to determine sublethal concentrations, and thus enable the evaluation of extract effects on parasitoid development from treated hosts. Direct effects of the extract through ingestion or contact (topical application) on adult wasp survival were also evaluated. An extract concentration of 0.2% was selected for parasitoid tests, since it allowed butterfly larvae to survive and pupate at normal rates, while inducing sublethal effects manifested as lower body weight. The indirect effects of the extract, through parasitoid development on treated hosts, were seen only in a female-biased sex ratio, without significant effects on either cocoon formation time, number of cocoons or adult parasitoids emerged. Adult wasps suffered increased mortality when their food was treated with extract, but were unaffected by topical application. These results suggest that M. azedarach extracts could represent an interesting tool for integrated pest management of C. lesbia populations.